Dampak faktor-faktor makroekonomi terhadap tingkat pengangguran di Provinsi Bali tahun 2020-2024 - Putri Desika Ayu; I Made Sara; Dewa Putu Yudi Pardita (Journal of Economics Research and Policy Studies, 2026)
Open unemployment remains a major challenge in regional economic development, particularly in Bali Province, which heavily depends on the service and tourism sectors. This study aims to analyze the impact of Gross Regional Domestic Product, Minimum Wage by Regency/City, and Labor Force Participation Rate on the open unemployment rate in regencies/cities of Bali Province during the period 2020–2024. The study employs a quantitative, panel-data regression approach using secondary data from the Central Statistics Agency. The results show that all variables have a significant effect on the open unemployment rate simultaneously. Partially, Gross Regional Domestic Product has a negative but insignificant relationship, while the Minimum Wage by Regency/City has a negative and significant effect. The Labor Force Participation Rate also has a negative but insignificant effect. These findings indicate that economic growth in Bali has not been fully inclusive in generating employment, while minimum wage policies and increased labor force participation help reduce unemployment. The implications highlight the importance of policies that promote more inclusive economic growth, strengthen labor-intensive sectors, and improve workforce quality to support sustainable employment absorption.